DETERMINATION OF ORGANIZATIONAL CLIMATE, COMPETENCY, AND COMPENSATION TOWARD JOB SATISFACTION WITH CAREER DEVELOPMENT AS INTERVENING VARIABLE AT IMMIGRATION OFFICE OF BATAM USING PARTIAL LEAST SQUARE - Putri, Shinta Buana; Fachruddin, Fachruddin; Wibisono, Chablullah (Universitas Batam, 2019)
In this study, researchers used respondents data, such as gender, level of education, and class / rankÂ of respondents to be able to provide information about the characteristics of respondents. Where from the questionnaire distributed questionnaire as many as 169 respondents. This research is the result of a field study to obtain a questionnaire answer data that measures five main variables in this study, namely organizational climate, competency, compensation, job satisfaction and career development. Data analysis with parametric and non parametric statistics using SEM-PLS (Structural Equation Modeling-Partial Least Square) regarding research variables, instrument test, normality test, hypothesis test, and discussion of the results of hypothesis testing and Path Path Analysis. This study uses path analysis (path analysis) to test the pattern of relationships that reveal the influence of variables or a set of variables on other variables, both direct influence and indirect influence. Calculation of the path coefficient in this study is assisted by Smart PLS Ver 3.0. To find out the direct and indirect effects between variables, it can be seen from the results of the calculation of the path coefficient while to find out the significance. The results showed work Organizational Climate, Competency, Compensation significantly influence Job Satisfaction Through Career Development at Immigration Office of Batam